Endovascular treatment of symptomatic Budd–Chiari syndrome – in favour of early transjugular intrahepatic portosystemic shunt. Issue 6 (June 2016) - Rosenqvist, Kerstin; Sheikhi, Reza; Eriksson, Lars-Gunnar; Rajani, Rupesh; Rorsman, Fredrik; Sangfelt, Per; Nyman, Rickard
Abstract : Introduction: Treatment of Budd–Chiari syndrome (BCS) has shifted from mainly medical treatment, with surgical shunt and orthotopic liver transplantation (OLT) as rescue, to medical treatment combined with an early endovascular intervention in the past two decades. Purpose: To assess the safety and efficiency of endovascular treatment of symptomatic patients with BCS and to compare mortality with symptomatic BCS patients in the same region treated with only sporadic endovascular techniques. Methods: This was a retrospective review of clinical data, treatment and survival in 14 patients diagnosed with BCS and treated with endovascular methods from 2003 to 2015. A national epidemiology study of BCS from 1986 to 2003 was used for comparison. Results: Thirteen of the 14 patients eventually had transjugular intrahepatic portosystemic shunt (TIPS), four after previous liver vein angioplasty. TIPS were performed with polytetrafluoroethylene-covered stents and technical success was 100%. Calculated preinterventional prognostic indices indicated a high risk of TIPS dysfunction, OLT and death. However, only one patient died and one had an OLT, and the 1- and 2-year primary TIPS-patency was 85 and 67%, respectively. Episodes of de-novo hepatic encephalopathy occurred in three patients. Overall 1- and 5-year transplantation-free survival was 100 and 93% compared with 47 and 28%, respectively, in 1986 to 2003. Conclusion: TIPS seems to be a safe and effective treatment for symptomatic BCS and there is an obvious improvement in transplantation-free survival compared with conservatory medical treatment. It should, therefore, be considered early, as first-line intervention, in patients with insufficient response to medical treatment.